Dynamics of Village Head Election Arrangements - Wantu, Fence M; Tome, Abdul Hamid (Jambura Law Review, 2021)
This study aims to analyze the arrangement of village head elections from the beginning of independence until now. The method used in this study is the normative legal research method regarding primary and secondary legal materials. The legal materials obtained are then analyzed descriptively. The results showed that the arrangement of the selection of village heads has its dynamics in line with the development of the politics of the law of the state that occurs. The existing legal, political conditions influence determining the conditions for the candidates of village heads. Although it has been regulated for a long time, it turns out that all existing laws and regulations have not made arrangements related to the provisions of the supervisory mechanism and the mechanism of resolving disputes for the selection of village heads. Regulation of the Minister of Home Affairs on the Selection of Village Heads attaches supervisory duties to the regional election committee. However, it does not make arrangements for how the surveillance process should be conducted.On the one hand, in the regulation, it is expressly mentioned the existence of supervisors in the implementation of village head elections. Nevertheless, it did not specify who the superintendent was. Similarly, the settlement of disputes for the selection of village heads is left entirely to the Regent /Mayor to do so. Granting authority to the head of the region can undermine the democratic process built by the village through the selection of village heads.